Association between Altered Thyroid Function and Prediabetes in Diet-Induced Prediabetic Male Sprague Dawley Rats - Malishca Pillay; Palesa Mosili; Akinjide Akinnuga; Ntethelelo Sibiya; Phikelelani Ngubane; Andile Khathi (Diabetology, 2023)
There is a correlation between the existence of type 2 diabetes mellitus (T2DM) and the development of thyroid disorders. Prediabetes is a progressive state of moderate insulin resistance that often precedes the onset of T2DM. However, the association between prediabetes and thyroid function is unknown. This study assessed changes in markers of thyroid function in diet-induced prediabetes. Twelve male Sprague Dawley rats (n = 12) were randomly assigned into two groups. Rats in the non-prediabetic (NPD) group were fed a standard rat diet, while rats in the prediabetic (PD) were fed a high-fat high-carbohydrate diet for 20 weeks to induce prediabetes. Thereafter, fasting blood glucose levels were measured. Plasma samples were assessed for triiodothyronine (T3), thyroxine (T4), thyroxine peroxidase (TPO) antibody, insulin, and glycated hemoglobin (HbA1c) concentrations. The elevated blood glucose, HbA1c, and plasma insulin levels coincided with increased T3 and reduced T4 levels in the PD group when compared to the NPD group. There was also an increase in the concentration of TPO antibodies in the PD group. Additionally, there was a significant correlation between the thyroid hormone concentrations and HbA1c levels. In conclusion, these results indicated that there is a positive association between thyroid dysfunction and diet-induced prediabetes in rats.